High-frequency periodic patterns driven by non-radiative fields coupled with Marangoni convection instabilities on laser-excited metal surfaces. (1st August 2020) - Rudenko, A.; Abou-Saleh, A.; Pigeon, F.; Mauclair, C.; Garrelie, F.; Stoian, R.; Colombier, J.P.
Graphical abstract: Abstract: The capability to organize matter in spontaneous periodic patterns under the action of light is critical in achieving laser structuring on sub-wavelength scales. Here, the phenomenon of light coupling to Marangoni convection flows is reported in an ultrashort laser-melted surface nanolayer destabilized by rarefaction wave resulting in the emergence of polarization-sensitive regular nanopatterns. Coupled electromagnetic and compressible Navier-Stokes simulations are performed in order to evidence that the transverse temperature gradients triggered by non-radiative optical response of surface topography are at the origin of Marangoni instability-driven self-organization of convection nanocells and high spatial frequency periodic structures on metal surfaces, with dimensions down to λ /15 ( λ being the laser wavelength) given by Marangoni number and melt layer thickness. The instability-driven organization of matter occurs in competition with electromagnetic feedback driven by material removal in positions of the strongest radiative field enhancement. Upon this feedback, surface topography evolves into low spatial frequency periodic structures, conserving the periodicity provided by light interference.